WONDERFUL OR AWFUL? STUDENT-TEACHERS’ CLASSROOM MANAGEMENT EXPERIENCES IN PRACTICUM TEACHING - Saiful Akmal; Khairil Razali; Yuni Setia Ningsih; Rosdiana (English Education Department, 2019)
This study is aimed at probing the strengths and weaknesses of classroom management experienced by student teachers at Department of English Language Education, UIN Ar-Raniry during the internship program at designated schools. Data collection was based on qualitative semi-structured interview with 8 student teachers chosen by purposive sampling from the 250 fourth student teachers at the English Language Education Department in 2017/2018 academic year. The findings of the current study indicated that group discussion method applied in the classroom enable more efficient classroom management. On the other hand, it is found that student teachers still experienced great deal of anxiety in managing the classroom. This may cause serious problems when facing real classroom management following their graduation as real teachers.